The Factors Affecting the Profitability of Conventional Banks Listed on the Indonesia Stock Exchange - Winda Anggreni Br Sembiring; Anita Roosmalina Matusin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research aims to determine the factors that affect on profitability of conventional banks listed on the Indonesia Stock Exchange during the 2018-2022 period, as many as 37 banks. The sampling method used is purposive sampling and panel data regression analysis. The independent variables in this research are deposit ratio, loan ratio, equity ratio, non-interest income, and liquidity ratio. The dependent variable in this research is return on assets. The research results found that non-interest income has a positive influence on return on assets, while deposit ratio, loan ratio, equity ratio, and liquidity ratio have no influence on non-performing loans. The companies in the banking sector are expected to increase the non-interest income to raise the profitability of the banks. Also, the investors are expected to choose banks with high non-interest income to maximize the return of their investment.